Ultra-Wideband, Short-Pulse Electromagnetics 7 - Sabath, Frank; Mokole, Eric L.; Schenk, Uwe.; Nitsch, Daniel; SpringerLink (Online service) (New York, NY : Springer New York, 2007)
Ultra-wideband (UWB), short-pulse (SP) electromagnetics are now being used for an increasingly wide variety of applications, including collision avoidance radar, concealed object detection, and communications. Notable progress in UWB and SP technologies has been achieved by investigations of their theoretical bases and improvements in solid-state manufacturing, computers, and digitizers. UWB radar systems are also being used for mine clearing, oil pipeline inspections, archeology, geology, and electronic effects testing. Ultra-Wideband Short-Pulse Electromagnetics 7 presents selected papers of deep technical content and high scientific quality from the UWB-SP7 Conference, including wide-ranging contributions on electromagnetic theory, scattering, UWB antennas, UWB systems, ground penetrating radar (GPR), UWB communications, pulsed-power generation, time-domain computational electromagnetics, UWB compatibility, target detection and discrimination, propagation through dispersive media, and wavelet and multi-resolution techniques. This book serves as an essential for scientists and engineers working in these applications areas.
Electromagnetic Theory & Modelling -- Time-Domain Computational Techniques -- Antennas -- Pulsed-Power -- UWB Interaction -- UWB & Transient Metrology -- Radar Systems -- Detection, Target Identification and Signal Processing -- UWB Communication -- Broadband Systems and Components.
Keywords: Physics; Optics; Electrodynamics; Microwaves; Optical engineering; Electronics; Microelectronics; Electronic circuits; Physics; Optics and Electrodynamics; Circuits and Systems; Microwaves, RF and Optical Engineering; Electronics and Microelectronics, Instrumentation; Electronic books